Assessment of cultivation parameters influencing pectinase production by Aspergillus niger LFP-1 in submerged fermentation - Mohd Taufiq Mat Jalil; Nurul Aili Zakaria; Nor Hawani Salikin; Darah Ibrahim (Journal of Genetic Engineering and Biotechnology, 2023)
Abstract Background Pectinase is helpful in food and beverage industries, particularly in the preparation of fruit juice, the extraction of vegetable oil, and the fermentation of coffee. The current work aimed to screen Aspergillus niger LFP-1, a recently identified fungal strain, for its ability to produce pectinase and to ascertain the contribution of various physicochemical factors to pectinase production. Results The primary and secondary pectinase activity screenings by Aspergillus niger LFP-1 were performed using pectin screening agar and shake flask system, respectively. The finding revealed that the locally isolated strain is able to secrete favourable pectinase production. Before improvement, the pectinase production was 0.88 ± 0.09 U/mL. However, the improved conditions such as 6 days of the cultivation period, agitation speed of 150 rpm, inoculum size of 1 × 106 spores/mL, 2.5% (w/v) citrus pectin, and 0.4% (w/v) ammonium nitrate could significantly increase pectinase production up to 7.41 ± 0.24 U/mL, representing an 88% increase. In this study, supplementing 2.5% (w/v) citrus pectin to the culture medium as a carbon source increased enzyme production by up to 3.07 ± 0.17 U/mL. Meanwhile, 0.4% (w/v) ammonium nitrate was used as a nitrogen source yielding the highest enzyme activity with a value of 6.86 ± 0.07 U/mL. Conclusion Thus, the locally isolated fungal strain, A. niger LFP-1 has outstanding pectinase-producing capability and can be utilized for the commercial production of pectinase. The improved cultural conditions significantly increase pectinase production and shorten the incubation period from 8 days (before improvement) to 6 days (after improvement).